Efficacy and Safety of Regorafenib With 2/1 Schedule for Patients ≥ 75 Years With Metastatic Colorectal Cancer (mCRC) After Failure of 2 Lines of Chemotherapy - Petrioli, Roberto; Chirra, Martina; Messuti, Luciana; Fiaschi, Anna Ida; Savelli, Vinno; Martellucci, Ignazio; Francini, Edoardo (Clinical colorectal cancer, 2018)
Regorafenib was shown to improve survival of patients with metastatic colorectal cancer resistant or unfit for all available therapies. Data on the efficacy and safety of regorafenib in elderly patients are scarce. In this small analysis, regorafenib administered with a modified schedule (2 weeks-on/1 week-off) to patients who were aged ≥ 75 and non-frail with late-stage metastatic colorectal cancer appears to be tolerable and effective. In the CORRECT (patients with metastatic COloRectal Cancer treated with REgorafenib or plaCebo after failure of standard Therapy) trial, regorafenib was proven to extend survival of patients with metastatic colorectal cancer (mCRC) that progressed after all available therapies. Grade 3 to 4 toxicity occurred in 54% of patients, and data on the activity and tolerability of regorafenib in elderly patients were scarce. The aim of this study was to evaluate the efficacy and safety of an alternative schedule, 2-week-on treatment and 1 week-off (2/1 schedule), of regorafenib for elderly patients with mCRC. Patients ≥ 75 years with mCRC who progressed after oxaliplatin- and irinotecan-based chemotherapy received regorafenib on a 2/1 schedule. Potentially frail subjects were identified by G8 screening tool and excluded. The 2-month disease-control rate was the primary endpoint, and the secondary endpoints included safety, progression-free survival (PFS), overall survival (OS), and objective response rate. Between February 2014 and May 2017, 23 patients with mCRC were recruited at our institution. No partial or complete responses were observed, and the stable disease and disease-control rate were 52.2%. The median PFS was 4.8 months (95% confidence interval, 3.8-6.3 months), and the median OS was 8.9 months (95% confidence interval, 6.9-10.6 months). Adverse events were uncommon, and the most frequent grade 3 toxicity adverse events were hand-foot skin reaction (9%) and fatigue (9%). Toxicity-related dose reductions and discontinuations occurred in 5 and 2 patients, respectively. Regorafenib administered with a modified 2/1 schedule to patients who were aged ≥ 75 years and non-frail with treatment-refractory mCRC seems to be tolerable and achieve encouraging results in terms of PFS and OS.